2022
DOI: 10.1177/03936155221096690
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic association between NLRP3 inflammasome expression level and operable pancreatic adenocarcinoma

Abstract: Background The NLRP3 inflammasome is significantly associated with tumor development and metastasis in various malignancies. However, the significance of the NLRP3 inflammasome in pancreatic adenocarcinoma has not been fully determined. Therefore, we try to evaluate the expression of the NLRP3 inflammasome in pancreatic adenocarcinoma and analyzed its prognostic significance. Methods This cohort study enrolled 98 patients with primary pancreatic adenocarcinoma who received curative surgery. The NLRP3 inflammas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Consistently, IL1β levels were found elevated in PDAC samples ( 6 ). Notably, recent studies have reported a positive correlation between NLRP3 expression and reduced survival in patients with PDAC, reinforcing the hypothesis of an important role for NLRP3 in PDAC progression ( 13 ). In humans, 14 members of the NLRP family have been identified ( 41 ), herein we demonstrated that NLRP3 mediates the increase in IL1β production in PDAC; however, the activation of other members of the family was not investigated in this study; therefore, it cannot be excluded.…”
Section: Discussionsupporting
confidence: 55%
“…Consistently, IL1β levels were found elevated in PDAC samples ( 6 ). Notably, recent studies have reported a positive correlation between NLRP3 expression and reduced survival in patients with PDAC, reinforcing the hypothesis of an important role for NLRP3 in PDAC progression ( 13 ). In humans, 14 members of the NLRP family have been identified ( 41 ), herein we demonstrated that NLRP3 mediates the increase in IL1β production in PDAC; however, the activation of other members of the family was not investigated in this study; therefore, it cannot be excluded.…”
Section: Discussionsupporting
confidence: 55%
“…We also observed a difference in the ASC amount between cell lines, but a higher ASC amount was not associated with more ASC speck formation. A high expression of ASC protein is often used as a marker for inflammasome formation in multiple types of cancer [21,31,[43][44][45][46][47][48][49]. The ASC protein levels [13] and PYCARD gene expression [50] (Figure 5e) were increased in the PDAC tissue, but our results imply that the ASC amount alone may be a poor marker for inflammasome formation.…”
Section: Discussionmentioning
confidence: 64%
“…A high gene expression of PYCARD was detected in the PDAC primary tumors and metastases (Figure 5e) and correlated with poor survival (Figure 6d). Further, an increased ASC amount has been associated with pancreatic cancer in patient material [21]. We therefore decided to investigate whether the amount of ASC protein was connected with inflammasome assembly in the PDAC cell lines.…”
Section: Bxpc-3 Cells Have a High Total Asc Levelmentioning
confidence: 99%
See 1 more Smart Citation